1989
DOI: 10.3109/13813458909104543
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Content, Influx and Accumulation Rate, and Catecholamine Biosynthesis Measuredin Vivo, in the Central Nervous System and in Peripheral Organs of the Young Rat. Influence of Neonatal Hypo- and Hyperthyroidism

Abstract: The influence of neonatal hypo- and hyperthyroidism on different aspects of tyrosine metabolism in the hypothalamus, striatum, brainstem, adrenal glands, heart and brown adipose tissue (BAT) were studied in 14-day old rats. The synthesis rate of catecholamines (CA) was also determined in vivo after the injection of labelled tyrosine. Hypothyroidism increases tyrosinaemia and endogenous tyrosine concentration in the hypothalamus and BAT. Hyperthyroidism decreases tyrosinaemia and endogenous tyrosine levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Hypothyroidism caused tyrosinaemia (tyrosine accumulation) in the brain, adrenal, heart, etc. (Diarra et al 1989) and the genetically hypothyroid mouse (non-functional thyroid due to defective TSH receptor) showed significantly fewer (40%) dopamine (TH-positive) neurons in the substantia nigra and adjacent ventral tegmental area (Kincaid 2001). The reported effects of hypothyroidism on TH are at variance and seem to be influenced by several factors including its nature of induction.…”
Section: Discussionmentioning
confidence: 87%
“…Hypothyroidism caused tyrosinaemia (tyrosine accumulation) in the brain, adrenal, heart, etc. (Diarra et al 1989) and the genetically hypothyroid mouse (non-functional thyroid due to defective TSH receptor) showed significantly fewer (40%) dopamine (TH-positive) neurons in the substantia nigra and adjacent ventral tegmental area (Kincaid 2001). The reported effects of hypothyroidism on TH are at variance and seem to be influenced by several factors including its nature of induction.…”
Section: Discussionmentioning
confidence: 87%
“…Thyroid hormones have been shown to regulate the levels of dopamine receptors [74, 75] and the activity of tyrosine hydroxylase [76–78], the rate-limiting enzyme of the cathecolaminergic pathway. Moreover, it has been suggested that dopamine may be inhibitory of TSH secretion [59], as treatment with dopamine blockers lead to increase in TSH level or to subclinical hypothyroidism [79], and that hypothyroidism can lead to increased dopamine receptor sensitivity [74].…”
Section: Thyroid Hormones and Schizophrenia: Relationship With Neumentioning
confidence: 99%
“…7 Stored in specialized cellular vesicles until required, the catecholamines dopamine (DA) and norepinephrine (NE) predominantly act as neurotransmitters within the brain, whereas NE and another catecholamine derived from DA, epinephrine (E), are the major peripheral catecholamines synthesized in the medulla of the adrenal gland. 8 Endogenous production of catecholamines has also been found in the heart, 9,10 immunocompetent cells, 6 gut 11 and kidneys. 12,13 Upon release of catecholamines during neurotransmission in the brain, mechanisms around the synapse clear 80-90% of the neurotransmitter, but spillover of excess catecholamines may act on targets at a distance and enter plasma.…”
Section: Introductionmentioning
confidence: 99%